Sex Education in Pesantren: The Study of Kitab on Sex Manuals in Pesantren in Bandung, West Java - Irma Riyani (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2019)
This paper examines the sexual agency exercised by married Muslim women in Bandung, Indonesia, in their marital relationships. Dominant discourses teach that women should obey their husbands, and most women believe that they should serve their husbands sexually whenever required. Sex is a taboo subject and women should not discuss sex or initiate sex. Their sexual desire is not acknowledged. However, in-depth interviews with 42 married women, and some husbands, found that a few exceptional women managed to challenge or negotiate around these dominant discourses. The paper examines their exercise of agency with regard to the initiation of sex, positions and practices that they prefer, their ability to say no to sex, ways to avoid having sex and their demand for mutual pleasure in sex.